2012
DOI: 10.1152/ajpregu.00518.2011
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of isothiocyanates on blood-CSF barrier disruption induced by oxidative stress

Abstract: The choroid plexuses (CPs) form the blood-cerebrospinal fluid (CSF) barrier (BCSFB) and play an important role in maintaining brain normal function and the brain response to injury. Many neurological disorders are associated with oxidative stress that can impact CP function. This study examined the effects of isothiocyanates, an abundant component in cruciferous vegetables, on H(2)O(2)-induced BCSFB disruption and CP cell death in vitro. It further examined the potential role of a transcription factor, nuclear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…Sulforaphane ingested orally has been shown to induce phase II enzymes such as glutathione-S-transferase, NQO1, and hemoxygenase-1 (HO-1) in the human upper airway (39). Other studies have shown that, following traumatic brain injury, early sulforaphane treatment upregulates Nrf2-dependent genes for GST and HO-1, attenuates the loss of expression of the tight junction proteins occludin and claudin-5, reduces endothelial cell death, and preserves blood-brain barrier function (12,43,44). In the blood-brain barrier, enhancing the expression of Nrf2-driven genes with a specific peptide that binds to Keap1 and releases Nrf2 into the nuclear compartment significantly reduced endothelial barrier compromise after traumatic brain injury (45).…”
Section: Discussionmentioning
confidence: 99%
“…Sulforaphane ingested orally has been shown to induce phase II enzymes such as glutathione-S-transferase, NQO1, and hemoxygenase-1 (HO-1) in the human upper airway (39). Other studies have shown that, following traumatic brain injury, early sulforaphane treatment upregulates Nrf2-dependent genes for GST and HO-1, attenuates the loss of expression of the tight junction proteins occludin and claudin-5, reduces endothelial cell death, and preserves blood-brain barrier function (12,43,44). In the blood-brain barrier, enhancing the expression of Nrf2-driven genes with a specific peptide that binds to Keap1 and releases Nrf2 into the nuclear compartment significantly reduced endothelial barrier compromise after traumatic brain injury (45).…”
Section: Discussionmentioning
confidence: 99%
“…Of importance, cytoprotective transporters and enzymes are under the transcriptional regulation of nuclear factors, which are expressed in the choroid plexuses [73]. The nuclear factor erythroid 2-related factor 2 pathway, in particular, represents an attractive target to protect the BCSFB and induce its antioxidant capacities in neurological disorders associated with oxidative stress [168].…”
Section: Pro-oxidant Speciesmentioning
confidence: 99%
“…Even more interesting, recent findings demonstrated that 6-MSITC provided neuroprotection against cytotoxicity induced by oxidative stress in rat striatal cultures by raising the intracellular GSH content (Mizuno et al, 2011). Although other isothiocyanates have shown interesting neuroprotective effects Tarozzi et al, 2012;Xiang et al, 2012), to the best of our knowledge, no studies have been done before on the 6-MSITC neuroprotective activity in an in vivo PD model.…”
Section: Introductionmentioning
confidence: 98%